2010
DOI: 10.1364/oe.18.006131
|View full text |Cite
|
Sign up to set email alerts
|

Single frequency operation of a tunable injection-seeded Nd:GSAG Q-switched laser around 942nm

Abstract: Single frequency operation of a diode-pumped tunable injection-seeded Nd:GSAG Q-switched laser around 942nm was demonstrated. With a three-mirror ring cavity, the single frequency laser pulse with output energy of 13.2mJ was obtained at a repetition rate of 10Hz. The linewidth of the single frequency laser was less than 100MHz. The wavelength of the single frequency Nd:GSAG laser can be tuned from 942.38nm to 943.10nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In 20 measurements, the energy stability was observed as better than 3%. It shows significantly improved stability of the pulse energy compared to our previous work [19], where the energy stability was ∼20%.…”
Section: Output Pulse Energy and Beam Qualitymentioning
confidence: 47%
See 3 more Smart Citations
“…In 20 measurements, the energy stability was observed as better than 3%. It shows significantly improved stability of the pulse energy compared to our previous work [19], where the energy stability was ∼20%.…”
Section: Output Pulse Energy and Beam Qualitymentioning
confidence: 47%
“…The difference of the pulse buildup time was within 10 ns and the pulse energy fluctuation was lower than 3%. Compared to previous works [7,10,12,14,19], the locking probability and operation stability were greatly improved.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Strohmaier et al [5] and Zhang et al [6] also reported the diode-pumped Nd:GSAG and Nd:YGG lasers at 942 nm and 935 nm. Recently, stable LD-pumped modelocked and tunable single frequency injection-seeded Q-switched Nd:GSAG lasers around 942 have been demonstrated for the further development of quasi-three-level Nd 3+ lasers [7,8].…”
Section: Introductionmentioning
confidence: 99%